Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


LHS:     cosec(65+a) - sec(25-a)
          = sec(90-(65+a))-sec(25-a)
          = sec(90-65-a)-sec(25-a)
          = sec(25-a)-sec(25-a)
          = 0 which is RHS

therefore, LHS=RHS
i.e., Cosec[65 degree+a]-sec[25 degree-a]=0
Hence, it is proved.
3 4 3
Please click on thanks and mark it as best.. hope ir helps you..
thanyou you
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts